Enfrentamiento de la hernia inguinal en el siglo XXI - Albán G., Marco; Rappoport S., Jaime; Silva S., Juan Jorge; Debandi L., Aníbal (Revista Hospital Clínico Universidad de Chile, 2010)
Inguinal hernia represents one of the three most frequent surgical pathologies in surgical practice. About 5% of the population has the risk to develop a hernia. Clinical picture presents as a inguinal bulge, pain related with efforts or both. The confirmation of the diagnosis usually is mainly on clinical basis. Ultrasound scan is a useful tool. Inguinal hernia represents a public health problem, according to the volume of the pathology, cost involved and labor incapacity. The etiology is multifactorial. Modern concepts are related to collagen disorders. In this review, anatomical concepts are presented and modern nomenclature is included. More than 100 surgical techniques have been described for the treatment of inguinal hernia. At present, techniques based in the concept of tension free surgery are the more accepted. Lichtenstein technique, with the use of surgical mesh is the gold standard for the treatment of a primary inguinal hernia. Early surgical treatment is recommended to avoid complications such strangulation